Ibn Khaldun's concept of Economic, Social and Political Relations - Hasna Maliha (Islamic Economics and History, 2022)
This study tries to examine the relationship between several economic and political variables proposed by Ibn Khaldun. This theory is called 'Ashabiyah'. There are several important findings. When a country has a good level of economic growth, the physical development of a country is relatively good and positive. Vice versa. Second, variable N (society) has a significant effect on the level of development of a country. This conclusion is in line with Ibn Khaldun's thesis which says that the quantity and quality of human resources, especially those who work productively, will be able to improve the economy and development of a country. Another conclusion is that a country that is relatively stable economically, the government that is in office at that time will tend to have the strength to survive in its leadership dynasty. In addition, with good economic conditions and the wealth of a country, the position and conditions of the people will improve.